Pengaruh Pembelajaran Kooperatif TGT dengan Metode GASING Terhadap Pemahaman Konsep Matematis Perkalian Dua Angka di SD - Maulida, Shelly Ainun; Isrokatun, Isrokatun; Julia, Julia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
This research aims to determine the influence of TGT type cooperative learning using the GASING method on students' understanding of the mathematical concept of multiplying two numbers. This research uses quantitative research methods with a quasi-experimental research type and a Nonequivalent Control Group Design research design. The population taken was all elementary schools in South Sumedang District, with the research sample being class IV students at SDN Sukaraja I, totaling 60 students. The research instrument is a test in the form of essay questions regarding understanding the mathematical concept of multiplying two numbers. The validity of the instrument is carried out through expert judgment on several experts and testing the instrument on students who then carry out validity and reliability tests. The data were analyzed by comparing the gain values of the control and experimental classes which had been carried out by normality tests, homogeneity tests and research hypothesis tests. The results of this research show that TGT cooperative learning using the GASING method has an influence on understanding the mathematical concept of multiplying two numbers as evidenced by an increase of 0.56 in the experimental class, higher than the increase in the control class of 0.26.